Morphological Words Awareness in Reading Text Comprehension by Indonesian EFL Teachers - Eusabinus Bunau (Indonesian Journal of EFL and Linguistics, 2023)
Since English is a foreign language in Indonesia and its teaching and learning is a text-based approach, it is essential to address the role of morphological words in the text. This current research aimed to investigate the awareness of English teachers on morphological words, specifically derivational and inflectional words, during reading text comprehension. The data used for this research was primary and secondary. A survey to collect the data was administered to 71 teachers from 24 (of 34) provinces attending an online professional in-service training program. The tool was a closed-ended questionnaire, adapting a 5-Likert scale with ten statements concerning derivational and inflectional words. The options of the questionnaire respectively are strongly aware, aware, hardly aware, unaware, and strongly unaware. The data were analyzed using the relative frequency distribution formula. Although it contradicts observation during the online training, this research revealed that the quality of awareness covering derivational and inflectional words was situated between 60%-80%, and the category is aware. The mean score of awareness of derivational and inflectional words are 76.29 and 74.05. The implication of this research to participants in implementing derivational and inflectional word awareness in reading text comprehension is immediate for their real teaching routines in the classroom.